Effects of Convective Heating on Entropy Generation Rate in a Channel with Permeable Walls - Adetayo Samuel Eegunjobi (Entropy, 2013)
This study deals with the combined effects of convective heating and suction/injection on the entropy generation rate in a steady flow of an incompressible viscous fluid through a channel with permeable walls. The model equations for momentum and energy balance are solved numerically using shooting quadrature. Both the velocity and temperature profiles are obtained and utilized to compute the entropy generation number. The effects of the key parameters on the fluid velocity, temperature, entropy generation rate and Bejan number are depicted graphically and analyzed in detail.